Role of L-, N- and T-type Calcium Channels in Achieving Maximum Analgesic and Minimum Toxic Effect of Tramadol - Mehmet Yilmaz; Bahadir Suleyman; Renad Mammadov; Durdu Altuner; Taha Abdulkadir Coban; Seval Bulut; Halis Suleyman; Resid Coskun (Polskie Towarzystwo Farmaceutyczne, 2024)
The aim of the study was to investigate the effects of lacidipine, amlodipine and benidipine on the analgesic activity and toxicity of tramadol. Rats (n=6/each group) were divided into five groups as control(CG), tramadol(TRD), lacidipine+tramadol(LTRD), amlodipine+tramadol(ATRD) and benidipine+tramadol(BTRD). Tramadol was administered once at a dose of 50 mg/kg and lacidipine, amlodipin, benidipin were administered at a dose of 4 mg/kg orally, once a day for 10 days. After the animals were sacrificed malondialdehyde(MDA) and total glutathione(tGSH) levels were measured in brain, heart, liver and kidney tissues. Troponin I(Tp I), alanine aminotransferase(ALT), aspartate aminotransferase(AST), blood urea nitrogen(BUN), and creatinine levels were determined in serum. Paw pain thresholds were measured 1 hour before and after drug administration. Analgesic effect of tramadol was increased the most by benidipine, while amlodipine and lacidipine increased it equally. Lacidipine failed to suppress MDA increase and tGSH decrease in brain tissue. Benidipine suppressed MDA increase and tGSH decrease in brain tissue better than amlodipine. All three drugs suppressed cardiac tissue oxidative stress and the release of TP I into the circulation. Lacidipine and amlodipine could not prevent tramadol-induced oxidative stress in liver and kidney tissues, whereas benidipine prevented excessive MDA increase and tGSH decrease. Benidipine significantly suppressed the increase of ALT, AST, BUN, and creatinine. Analgesic activity was 35.1% in TRD, 43.7% in LTRD 50.4% in ATRD and 67,5% in BTRD. Study results show that benidipine and tramadol co-treatment is better than co-treatment with lacidipine or amlodipine in achieving minimal toxic effects and maximum analgesia.